The differences of effectiveness of β-1,3-glukanase Vigna unguiculata and papain Carica papaya enzymes in hydrolysis of denture plaque - Retno Indrawati; Muhammad Luthfi; Erina Fatmala Yuli Andari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Accumulation of denture plaque can lead to pathological changes in oral mucosa, such as denture stomatitis, halitosis, and caries. Plaque matrix is mostly formed by protein (30%) and polysaccharide complexes. Thus, an alternative enzyme solution as denture cleanser is required for hydrolysis of denture plaque. Papain is a proteolytic enzyme hydrolyzing proteins, while β-1,3-glucanase is a hydrolase enzyme hydrolyzing polysaccharides. Purpose: This study aimed to analyze the differences of effectiveness of ß-1,3- glucanase Vigna unguiculata enzyme and papain Carica papaya enzyme in hydrolysis of denture plaque. Method: This research was a laboratory experimental research with post test only control group design. After using denture for 24 hours, the denture was soaked in a solution of 100 ml PBS, papain enzyme, and β 1-3 glucanase enzyme at a concentration of 0.5 mg/ml, 1 mg/ml, and 2 mg/ml for 10 minutes. The solution from plaque hydrolysis was soaked in PBS and vortex enzyme for 2 minutes, then soaked in ice water for 15 minutes, and centrifuged at 3000 rpm 5-10º for 10 minutes. The supernatant was separated and analyzed. Turbidity readings then were performed in spectrofotometer with a wavelength of 480 nm. Result: 2 mg/ml of ß-1,3 glucanase enzyme generated the highest values of hydrolysis with a mean percentage of 68.77% compared to papain enzyme (44.86 %). The lowest values of hydrolysis weregenerated by PBS with a mean percentage of 3.24%. Conclusion: ß-1,3-glucanase enzyme is more effective in hydrolysis of denture plaque than papain enzyme.